Healthy neighborhoods : understanding the effects of the urban environment on people's health - Cavalcanti, Rafaella dos Santos (2021)
This research project aims to verify how green and public open spaces in cities could affect people's health, more specifically on reducing non-communicable diseases - Particularly the cardiovascular and chronic respiratory diseases - based on the ODS 3 of the New Urban Agenda ‘to reduce premature deaths caused by these diseases by the year 2030’. Although the discussions about the features of the inhabited space and health are quite old, it is still very contemporary. This topic offers multiple possibilities of scientific exploration for several reasons, such as the persistence, the reappearance and the appearance of new diseases which have direct and indirect relationship with the characteristics of the city and the way that people live [1,2]. In addition, COVID-19 pandemic is showing the growing necessity in investments on open public spaces in Brazilian cities and other cities around the world, which promote safe social distance, short and different ways to move, especially walking and cycling [3,4]. Even though there is a dependency relationship between the quality of urban space and health, urban areas were developed based on an ideal model of the city without a direct correlation between their space arrangements and effects on people’s health. However, the discussion about the concept of a healthy city has begun in the1990s and many efforts have been made by Nordic countries to evaluate this relationship. Thus, different research has explored a vast repertoire of diseases that has helped to establish a cause and effect relationship which lead to more assertive formulation of urban and environmental policies in cities [5-8]. For example, it is possible to observe scientifically the effects of green spaces on diseases such as cardiovascular disease, obesity, heat stress, mental health and respiratory diseases. There are also several studies in Latin America on macro scale factors associated with health. Many of them carefully explore the theme of inequality, because it is an extremely striking feature in this region, and they use relatively sophisticated models to explain the relationship between city and health [3,9,10]. In Brazil, a vast quantity of studies are dedicated to the binomial health-sanitation. Also, in the literature, majority of studies are on a macro scale, and / or single correlation approach, that is, between a certain aspect of the urban environment and its impacts on people's health, such as green spaces and their relationship with cardiovascular diseases [11] and the effects of air pollution on the health of the population [12-14]. Thus, there is a huge opportunity in the exploratory field to study the effect of spatial arrangements from the Brazilian urban framework from the perspective of health. Especially considering the micro urban scale, mainly the design of the street and the neighborhood, and trying to understand the joint effect of the elements that make up these spaces and not just the effect of isolated aspects. In this context, some questions are important to make: which kind of correlation is possible to identify related to green and open public spaces and the occurrence of cardiovascular and chronic respiratory diseases that could result in a premature death of people? If there is a correlation, how and which elements of the arrangements of Brazilian urbanization are more significant to configure a system of green and open public spaces in our cities? In order to address these issues, this research is divided into two scales of analysis. The macro scale is associated with the concept that “health is created at the local level, in the settings of daily life, in neighborhoods and communities...” [15]. Here, it is also added the idea of neighborhood an extrapolation of 500 meters to its official limit, once the neighborhoods around also have influenced the lives of the local community [16]. The HDI-M1 was the criteria adopted to select the neighborhoods, since it is an indicator which is related to the concept of quality of life [17] that has health as an important part of its meaning [18]. Three neighborhoods in Recife/PE (Graças, Ipsep and Jordão) were selected with high, medium and low HDIMs, special arrangements, but similar demographic density, area and population. Urban Spatial Profile will be used to analyze the micro scale, considering the segment of street, which is ‘a methodology that starts from the establishment of a set of elements of the urban environment considered relevant to understand a behavior or social phenomenon’ [19,20]. At first, this research intends to study nine aspects that make up the atmosphere of the street and the neighborhood, which are: land use, accessibility, interface (public and private), constitution (gates), density, vegetation coverage index, proximity to parks and squares, cycle network and public gymnasiums. Finally, some scientific contributions are expected with this research: the production of knowledge about continuous assessment of the quality of urban space through the provision of a methodological tool; theoretical enrichment of urban design associated with issues of health and environmental resilience; and critical knowledge about the transformation of urban areas into healthy spaces.